KUALITAS PELAYANAN PADA SEKOLAH DASAR NEGERI INPRES 6/75 MADIDIR KOTA BITUNG - KURAMA, DIANA; LENGKONG, FLORENCE; KOLONDAM, HELLY (JURNAL ADMINISTRASI PUBLIK, 2020)
Schools have a role in providing quality services to the community where the role of the school against aÂ community in it is to educate the nation's life community intelligence can be developed through formal and non-formal education. Schools must be able to apply their roles to the community so that the community gets the effect of satisfaction on the services provided by the school, but the lack of a maximum level of service quality in schools is something that needs to be considered as in providing learning to students is not done optimally, Teacher Behavior who are less professional in serving the community and the performance of the teaching staff/teacher is not yet maximal in teaching students at school. The purpose of the study was to find out how the quality of service in Elementary Schools (SD) Inpres 6/75 Madidir Bitung City This research was conducted using a qualitative approach. Data Analysis Techniques In this study qualitative analysis of Miles and Huberman was used The results showed that the quality of service at the Inpres 6/75 Madidir State Primary School was classified as good in terms of existing service devices both teachers and staff at the school had done their job well so that the customers, students, and lever students were satisfied with the service. That in carrying out their duties, all service devices, both teachers and staff, in the Elementary School of Inpres 6/75 Madidir have followed the applicable rules. all staff in providing customer services so that they are satisfied with the way the service is carried out and by applying the nature of courtesy and friendliness so all work can be completed properly within the allotted time Keywords: Service Quality, Elementary School